COPING STRATEGIES FOR NAVIGATING GENDER AND AGING: WISDOM BY OLDER WOMEN WORKERS FROM PUNJAB, PAKISTAN - Meer, Yumna; Saeed, Dr. Sadia (South Eastern European Journal of Public Health, 2025)
The present study aims to explore coping strategies for navigating gender and aging among older working women from Punjab, Pakistan. In this qualitative study, the interpretative phenomenological approach (IPA) was employed. A total of twenty-four women, aged 60 and above, were recruited from Lahore, Rawalpindi, and Multan. All participants had previous formal sector work experience and were currently involved in post-retirement employment. Using purposive sampling, data was collected through semi-structured interview guide and observations checklist. To enhance the credibility and confirmability of the findings, member checking and peer review were incorporated into the process of IPA analysis. The study revealed various coping strategies employed by older Punjabi women for successful navigation of gender and aging in their old age. The strategies encompassed ongoing education and skill enhancement, enabling women to seek additional qualifications and certifications to stay competitive and pertinent in their respective domains. Adopting technology emerged as a vital approach, as numerous individuals developed new technical skills to improve their career prospects. Establishing professional connections via associations and conferences has been crucial for sustaining visibility and relevance in their areas of expertise. Support from mentors and connections with peers played a crucial role in advancing their careers and navigating gender obstacles. Resilience surfaced as a key focus, with women utilizing their life experiences to adapt and take charge in their respective domains. Last but not least, physical fitness and a healthy lifestyle was considered essential for sustaining professional engagement and a balanced work-family life, bolstered by flexibility and family cooperation, allows women to manage their dual responsibilities effectively..